(untitled) (Bangladesh Medical Journal Khulna, 2013)
Cervical cancer is the most common prevalent cancer that continues to be a major health care problem world wide. It is still an important cause of mortality and morbidity in the developing countries. An estimated 500,000 new cases of cancer cervix and 233.000 deaths occurred in the year 2000 and almost 80% of these cases happen in the developing countries. Hospital based statistics indicated cervical cancer constitutes 22-35% of the female cancer in different areas of Bangladesh and India. A retrospective study was done in Gynaecology and Obstetric department in KMCH between January 2004 to January 2009 to see the incidence, correlation of age, parity, socioeconomic condition and clinical staging, treatment and other risks factors of carcinoma cervix. Out of total 120 diagnosed cases of cervical cancer were evaluated regarding their clinio-demographic profile, appearance of growth, clinical staging and types of treatment done . The results showed 49% of patient were in the age group of 31-40 years, 26% were in the 41-50 years group, early age at first coitus (70%), most of the patients (82%) presented with advanced stage and referred for radiotherapy or chemo radiation. One in ten female cancers diagnosed world wide are cancers of the cervix and there is seven fold variation in the incidence of cervical cancer between the different regions of the world. The Incidence of invasive cervical carcinoma can be reduced by development of health education and promotion of national screening programme such as Visual Inspection of cervix (VIA), Colposcopy and vaccination against Human Pappiloma Virus (HPV). DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13623 Bang Med J (Khulna) 2012; 45 : 11-14